Alternate States of Consciousness and Biblical Research: Thc Contribution of John J. Pilch. (May 2017) - Craffert, Pieter F.
Nobody has done more than John Pilch to popularize the use of an ASC model for understanding the visions, sky journeys and other ecstatic experiences reported in biblical texts. He is to be credited for pointing out the ethnocentrism in traditional biblical research that do not take visions, soul journeys and the like seriously as culturally plausible human phenomena. He introduced the notion of alternate states of consciousness (ASCs), a well-known category in anthropological research, to biblical interpretation in an attempt to avoid the ethnocentrism that considers such reports as either nonhistorical or fictional. However, while avoiding ethnocentrism at this point he reintroduced it in two other ways. The first is by rejecting the so-called Western view of ASC experiences and secondly, by claiming that ASCs represent actual events that provide access to alternate reality—something that he considers to be absent from the reductionistic view of reality of Western cultures.